Ingestion of anthropogenic debris by marine fishes around New Zealand - Peter L. Horn (New Zealand Journal of Marine and Freshwater Research, 2022)
A summary is presented of the anthropogenic debris recorded up to 2020 in stomachs of marine fishes from New Zealand waters. This material (mainly plastics) was found in the stomachs of 28 species, with 24 of these species identified in two studies alone. Most of the New Zealand records were not identified in recently published global assessments of plastic ingestion by fish; the likely reasons for this are discussed. Consumption of anthropogenic debris by fish in New Zealand waters is probably a widespread phenomenon, particularly for inshore demersal species with an algal dietary component and for offshore pelagic species that prey on gelatinous biota. Based on currently available data, this behaviour may occur relatively less frequently in deeper water demersal habitats, although no studies investigating the ingestion of microplastic particles by fish in this section of the New Zealand marine environment have yet been completed. The likelihood of identifying plastics in fish diets is strongly dependent on the analytical method used.